Existence and nonexistence of radial solutions of the Dirichlet problem for a class of general k-Hessian equations - He, Jianxin; Zhang, Xinguang; Liu, Lishan; Wu, Yonghong (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, we establish the existence and nonexistence of radial solutions of the Dirichlet problem for a class of general k-Hessian equations in a ball. Under some suitable local growth conditions for nonlinearity, several new results are obtained by using the fixed-point theorem.